Efektivitas Terapi Bermain Fidget Spinner terhadap Nyeri Pasca Operasi Fraktur pada Anak - Abdul Rahman Wange; Andi Arniyanti (Universitas Baiturrahim, 2021)
Fracture is one of the most vulnerable injuries in children. Fracture is a disconnectionin bone continuity caused by trauma or physical exertion, the management of the fracture can be done with orthopedic surgery, namely by open reduction using internal fixation. Pain is a major problem in post operative fracture care Non pharmacological techniques that can be done to ward off postoperative pain in children are by doing play therapy, one of which is by using fidget spinner therapy. This literature review aims to analyze the effect of fidget spinner therapy on postoperative fracture pain.this game can distract children and give them something soothing to release pent up energy. Methods: This research explores quantitative evidence published in electronic databases such as pubmed, garuda, and google schoolar. Using a journal search strategy, I only came up with the results of one recent and relevant journal for inclusion in the final analysis. Results: I can see a significant effect in postoperative fracture pain intensity in the child after the patient was given fidget spinner therapy. Conclusion: From the results, it can be concluded that fidget spinner therapy is a non-pharmacological therapy that can reduce the pain scale in post operative fracture patients. It is hoped that parents will use this game in the handling of fracture pain in their children